2003
DOI: 10.1007/s10038-003-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridisation (FISH) analysis of chromosome segregation and interchromosomal effect in spermatozoa of a reciprocal translocation t(9,10)(q11;p11.1) carrier

Abstract: luorescence in situ hybridisation (FISH) analysis of chromosome segregation and interchromosomal effect in spermatozoa of a reciprocal translocation t(9,10)(q11;p11.1) carrier Abstract A couple was referred for exploration of repetitive abortions. The man was found to be a carrier of a balanced reciprocal translocation t(9;10)(q11;p11.1). The meiotic segregation of chromosomes 9 and 10 was analysed in 5,157 spermatozoa from this translocation carrier and in 15,255 spermatozoa from three control donors using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Nevertheless, in the literature, Escudero et al 29 and Brugnon et al 24 described frequencies of Adjacent II higher than Alternate or Adjacent I. Those same studies together with Martini et al, 30 Rives et al, 31 Van Assche et al, 32 Estop et al, 33 and Geneix et al, 34 also described high frequencies of 3:1 segregation products, a kind of segregation which in our population seemed to be the least frequent. Regarding that point, we think that it is important to note that segregation studies in reciprocal translocation carriers involve a greatly complicated methodological approach which, as has been discussed elsewhere, 35 can result in an overestimation of some specific types of unbalanced gametes.…”
Section: Tracing the Meiotic Behavior Of Reciprocal Translocationssupporting
confidence: 63%
See 1 more Smart Citation
“…Nevertheless, in the literature, Escudero et al 29 and Brugnon et al 24 described frequencies of Adjacent II higher than Alternate or Adjacent I. Those same studies together with Martini et al, 30 Rives et al, 31 Van Assche et al, 32 Estop et al, 33 and Geneix et al, 34 also described high frequencies of 3:1 segregation products, a kind of segregation which in our population seemed to be the least frequent. Regarding that point, we think that it is important to note that segregation studies in reciprocal translocation carriers involve a greatly complicated methodological approach which, as has been discussed elsewhere, 35 can result in an overestimation of some specific types of unbalanced gametes.…”
Section: Tracing the Meiotic Behavior Of Reciprocal Translocationssupporting
confidence: 63%
“…Alternatively, the presence of abnormal seminal parameters was also considered because an association between low semen quality and increased tax of aneuploid sperm has been described. 31,[42][43][44] In this sense, a recent study (Sarrate et al, unpublished results) has revealed a 14% incidence of this phenomenon in individuals with altered seminal parameters and a normal karyotype. Nevertheless, in the population of reciprocal translocation carriers analyzed in this work, the frequency of cases with increased percentages of aneuploidies rose to 50%.…”
Section: Interchromosomal Effectmentioning
confidence: 93%
“…In relation to the 3:1 segregation, in general there is an excess of monosomic spermatozoa compared to the complementary trisomic spermatozoa. Although an early selection during spermatogenesis of one of the two products has been noted (Mercier et al, 1998), technical problems cannot be discarded due to, for example, a reduction in the efficiency of hybridization in the smallest probes (Martini et al, 1998;Geneix et al, 2002;Rives et al, 2003).…”
Section: Comparison Of Results Obtained By Both Methodsmentioning
confidence: 99%
“…It has been proposed that the incidence of interchromosomal effects could be restricted to those translocation carriers with an altered semenogram (Pellestor et al, 2001). However, an altered semenogram is not always associated with interchromosomal effects (Rives et al, 2003), thus it is an open question as to which factors, if any, are responsible for the existence of interchromosomal effects in reciprocal translocation carriers.…”
Section: Comparison Of Results Obtained By Both Methodsmentioning
confidence: 99%
“…Indeed, several authors reported the occurrence of an ICE [Rousseaux et al, 1995;Pang et al, 1999;Rives et al, 1999;Blanco et al, 2000;Vegetti et al, 2000;Shi and Martin, 2001;Palermo et al, 2002;Anton et al, 2004;Douet-Guilbert et al, 2005;Machev et al, 2005;Vozdova et al, 2008] whereas others did not [Blanco et al, 1998;Honda et al, 1999;Estop et al, 2000;Oliver-Bonet et al, 2001Pellestor et al, 2001;Rives et al, 2003].…”
mentioning
confidence: 99%